Incidencia de la recreación en el área de cultura física para mejorar las aptitudes de los niños y niñas con síndrome de Down del instituto fiscal de educación especial de El Oro de la ciudad de Machala año lectivo 2012 – 2013. - Moreno Camacho, Darwin Rolando (2013)
This proposal is a program of recreational activities to improve the skills of children as it is very important in the formation and integral development of children. Through this institution it is offered a strategy of valuable learning routing it through the inclusion of targets and development of teaching skills and capabilities is achieved integrate the protagonists of the institution. During the investigation we use global methodology, analytical, inductive and deductive development of our thesis, while we carry out surveys to teachers, parents familiay observations students which allowed us to have a scientific idea to work and improve the skills of children with various recreational activities proposed in the aforementioned proposal.